2014 22nd International Conference on Pattern Recognition 2014
DOI: 10.1109/icpr.2014.367
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Microscopic Shape from Focus

Abstract: In this paper, we extend traditional Shape from focus (SFF) to the underwater scenario. Specifically, we show how 3D shape of objects immersed in water can be extracted from images captured under an optical microscope. Traditional SFF employs telecentric optics to achieve geometric registration among the frames. We extend conventional SFF to underwater objects under the assumption of negligible scattering. We establish that the property of telecentricity holds for objects immersed in water provided the numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The effect of refraction due to air-water interface is explicitly modeled by using the concepts of ellipse of refrax and refractive depth. Karthik et al [9] have shown that the conventional shape from focus can be extended to underwater objects. They consider an optical microscope imaging a 3D object through a still water surface.…”
Section: Introductionmentioning
confidence: 98%
“…The effect of refraction due to air-water interface is explicitly modeled by using the concepts of ellipse of refrax and refractive depth. Karthik et al [9] have shown that the conventional shape from focus can be extended to underwater objects. They consider an optical microscope imaging a 3D object through a still water surface.…”
Section: Introductionmentioning
confidence: 98%